1997
DOI: 10.2134/jeq1997.00472425002600050007x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Losses through Subsurface Tile Drainage in Conservation Reserve Program, Alfalfa, and Row Crop Systems

Abstract: Subsurface drainage of gravitational water from the soil profile through tiles is a common practice used to improve crop production on poorly drained soils. Previous research has often shown significant concentrations of nitrate‐N (NO3‐N) in drainage water from row‐crop systems, but little drainage research has been conducted under perennial crops such as those used in the Conservation Reserve Program (CRP). Four cropping systems (continuous corn, a corn‐soybean rotation, alfalfa, and CRP) were established in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
318
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(349 citation statements)
references
References 0 publications
25
318
3
3
Order By: Relevance
“…On average, RZWQM simulated a 14% reduction in drain flow under CC compared to CS. This is in agreement with other studies in the Midwest of the USA (Randall et al, 1997;Huggins et al, 2001), although Kanwar et al (1997) observed greater amounts of drain flow under CC than under CS rotation using 3 years of data (1990)(1991)(1992). As shown in Figs.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…On average, RZWQM simulated a 14% reduction in drain flow under CC compared to CS. This is in agreement with other studies in the Midwest of the USA (Randall et al, 1997;Huggins et al, 2001), although Kanwar et al (1997) observed greater amounts of drain flow under CC than under CS rotation using 3 years of data (1990)(1991)(1992). As shown in Figs.…”
Section: Simulated Long-term Crop Rotation and Tillage Effectssupporting
confidence: 92%
“…However, if 150 kg N/ha was applied to corn for both CC and CS, the model simulated 42% lower in nitrate-N loss (7.3 vs. 12.6 kg N/ha/year) and 32% lower in flow-weighted nitrate-N concentration (7.6 mg/L vs. 11.1 mg/L) for CC than for CS. Therefore, lower nitrate-N loss under CS was partially due to lower N application rate (Karlen et al, 1991;Randall et al, 1997;Huggins et al, 2001;Kladivko et al, 2004). Tillage had minimum effects on N loss to drain flow under CC as reported by Randall and Iragavarapu (1995), with slightly lower N loss simulated under NT than under MP (5%) and CP (5%) under CS (Table 4).…”
Section: Simulated Long-term Crop Rotation and Tillage Effectsmentioning
confidence: 69%
See 1 more Smart Citation
“…Considerable research has demonstrated that introducing perennial vegetation into an agricultural landscape dominated by annual crops of corn and soybeans can improve water quality (Schulte et al 2006;Dinnes et al 2002). Nitrate leaching beneath perennial vegetation is substantially reduced compared to annual crops (Randall et al 1997) because perennial vegetation maintains or increases soil organic nitrogen content (Drinkwater et al 1998), maintains greater soil water content (Brye et al 2000(Brye et al , 2001, and provides more evapotranspiration during vulnerable leaching periods in the spring and fall (Schilling et al 2008a).…”
mentioning
confidence: 99%
“…Changing precipitation patterns, combined with effects of increasing temperature on plant growth, mean that nutrient uptake patterns will change as agricultural systems adapt to a new climate. The increased susceptibility of nutrients to runoff and/or leaching resulting from climate change needs to be recognised and considered through changes in current nutrient management practices, including better timing of appropriate application rates (Nangia et al 2008), better targeting of fertiliser rates to match the distributions of soil and crop conditions within fields (Delgado and Berry 2008), intensification of plant water use through incorporation of cover crops (Kaspar et al 2007) or perennials (Randall et al 1997), and implementation of conservation practices that are able to trap and treat nutrient losses downstream of cropped fields (e.g. nutrient removal wetlands) (Tomer et al 2012).…”
Section: Implications For Aquatic Systemsmentioning
confidence: 99%